Empathy for Social Justice: The Case of Malala Yousafzai - Martínez García, Ana Belén (Journal of English Studies, 2019)
This essay demonstrates the effectiveness of human rights life narratives in garnering global support through their appeal to empathy. I focus on Nobel Peace Prize winner Malala Yousafzai’s autobiographical texts and their impact on lives outside the written pages, which is first and foremost of an empathic nature. The essay pays special attention to her childhood blog and her teenage autobiography, looking at the narrative strategies employed in both. Autobiographical texts are never neutral, enabling people to see themselves under a new light, spurring them to act. The delicate balance between witnessing and involvement hangs on the creation of an emotional bond.